1985
DOI: 10.1002/ajim.4700080207
|View full text |Cite
|
Sign up to set email alerts
|

Silicosis in slate pencil workers: I. An environmental and medical study

Abstract: An environmental and medical survey was undertaken in the slate-pencil industry in the central part of India. The industrial hygiene survey revealed that concentrations of free silica dust were very high. The medical survey, involving 593 workers, revealed that the prevalence of silicosis in this industry was 54.6%. Of these, 17.7% of workers had conglomerate silicosis (progressive massive fibrosis, PMF). The radiologic appearance of simple and conglomerate silicosis resembled closely the simple pneumoconiosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…The prevalence of silicosis is increased in developing countries, including Brazil, China, India and Vietnam. In India, the prevalence is increased in, for instance, workers in Kolar Gold Fields, Karnataka, and there is a high risk of silicosis in the slate pencil and agate grinding industry 3. Our patient had a total of 11 years of exposure to silica dust while working in a glass factory and later in a talc powder company.…”
Section: Discussionmentioning
confidence: 87%
“…The prevalence of silicosis is increased in developing countries, including Brazil, China, India and Vietnam. In India, the prevalence is increased in, for instance, workers in Kolar Gold Fields, Karnataka, and there is a high risk of silicosis in the slate pencil and agate grinding industry 3. Our patient had a total of 11 years of exposure to silica dust while working in a glass factory and later in a talc powder company.…”
Section: Discussionmentioning
confidence: 87%
“…Some farming, construction and demolition activities also contribute to the environmental exposure. Relation between occupational exposure and prevalence of silicosis and silico-tuberculosis has been established beyond doubt in many occupations (Hnizdo and Sluis-Cremer 1993;Saiyed et al 1985;Jiang et al 2001;Sadhu et al 1995). But there have been very few studies, which suggest that there can be non-occupational silicosis also.…”
Section: Introductionmentioning
confidence: 96%
“…The subsequent operations of collecting, sorting and packing are carried out manually near the cutting machine. Saiyed et al (1985) reported that total and respirable dust levels near cutting machine were 46.47 and 10.41 mg/m 3 respectively. Medical survey revealed that prevalence of silicosis in this industry was 54.6%.…”
Section: Introductionmentioning
confidence: 98%
“…Table 2 shows the prevalence of some of these diseases [4][5][6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Occupational Injuries and Diseasesmentioning
confidence: 99%
“…Surveys in some of these industries have shown high prevalence (12-54%) silicosis [5][6][7][8][9] . Free silica has been classified as carcinogen 30) .…”
Section: Silica Related Diseases Other Than Silicosismentioning
confidence: 99%